Determination of the Maximal Lactate Steady State in Obese Zucker Rats - Almeida, J. A.; Petriz, B. A.; Gomes, C.P. C.; Rocha, L.A. O.; Pereira, R. W.; Franco, O. L. (International Journal of Sports Medicine, 2013)
This study aims to identify the maximum lactate steady state (MLSS) in obese rats in order to provide a more effective tool in the exercise training prescription for this important animal model. To make such determination, obese (Zucker, n=5) (390.0±18.8 g) and lean (Wistar, n=5) (227.3±26.2 g) rats were studied. After adaptation of animals to treadmill, the MLSS was determined by using 3 different velocities (10 m.min − 1, 12.5 m.min − 1 and 15 m.min − 1 for Zucker and 15 m.min − 1, 20 m.min − 1 and 25 m.min − 1 for Wistar). The MLSS was defined as the highest blood lactate concentration that increased up to 1 mmol.L − 1 during constant exercise. In obese rats, the MLSS was found in a velocity considerably lower than in lean controls (12.5 m.min − 1 and 20 m.min − 1), respectively (p<0.05). Therefore, the identification of MLSS in obese Zucker rats is an important tool for exercise prescription and evaluation in obese rat models.
Keywords: MLSS; obese Zucker rat; treadmill running